Analisis Perbandingan Komposisi Karbon Dan Bubuk Tulang Sapi Dalam Proses Karburasi Padat Untuk Mendapatkan Nilai Kekerasan Tertinggi Pada Baja Karbon S-35 C - Nevada J.M. Nanulaitta; Eka R. M. A. P. Lilipaly (Industrial Engineering Study Program, Pattimura University, 2011)
S-35 C, is a low steel carbon type with 0,30% - 0,35% carbon composition, which has a low hardness. This matter can be overcome by changing the hardness of this steel through heat treatment process. Heat treatment method used in this experiment is pack carburizing method. Experiment results showed that with composition of 500 g of carbon and 0% beef bones with 15 minutes holding time, the hardness number increased as much as 116.90 HRC, there was 20.54 HRC number increased. With 10% of cow bones composition, hardness number became 118.39 HRC and 20.40 HRC number increased. HRC number became 122.20 and increased by 24.38 on 20% composition, and on 30% the hardness value became 130.36 HRC, increased until 32.05 HRC number. 40% composition showed increasing hardness number up to 133.34 HRC, with 35.08 HRC increased. And 50% composition showed 141.29 HRC number, increased until 43.95 HRC. 50% composition produce the highest increase of hardness number, this verified that the higher composition of cow bones makes higher increasing of hardness number in a heat treatment process deliver a harder steel, and also prove that beef bones can be used as a catalyst in pack carburizing process.